Short and Mid-term Outcomes of Percutaneous Perimembranous Ventricular Septal Defect Closure Using Amplatzer Duct Occluders Type II in Children and Adolescents - Hamid Amoozgar; Hamid Arabi; Mohammadreza Edraki; Amir Naghshzan; Nima Mehdizadegan; Hamid Mohammadi; Mohammadjavad Nobakhti; Kambiz Keshavarz (Iranian Journal of Medical Sciences)
Background: Percutaneous closure of perimembranous ventricular septal defects (pmVSD) with Amplatzer duct occluder type II (ADO II) is a novel method. The present study aimed to evaluate the short and mid-term outcomes of this method in children and adolescents. Methods: This retrospective study was conducted at Shiraz University of Medical Sciences from July 2019 to September 2023. It evaluated the outcomes of pmVSD closure using the ADO II. The effects on tricuspid regurgitation (TR), mitral regurgitation (MR), and aortic regurgitation (AR) were assessed, along with the presence of residual shunts and conduction disturbances. Data were analyzed using SPSS software (version 24.0). Fisher’s exact test and the Chi square test were employed for statistical analysis. P<0.05 was considered statistically significant.Results: This study included 102 patients. 31 patients had a short-term follow-up with a median of 79 (71.02, 97.01) days, and 71 patients had a mid-term follow-up with a median of 900 (384.25, 1044.75) days. The severity of TR, MR, and AR dropped to lower levels in most patients during follow-ups (P=0.003, P=0.030, and P=0.033, respectively). There was no significant difference in the valvar regurgitation changes between patients weighing more or less than 10 Kg or between those with short and mid-term follow-ups (P>0.05). There were no hemolysis, clot, embolization, death, or third-degree atrioventricular blocks. However, 2 (2%) patients developed a small residual shunt.Conclusion: Overall, ADO II appeared to be a safe transcatheter occlusion device for patients with pmVSD, and this method could reduce the severity of TR, MR, and AR with few complications.